The Association Between Market Liquidity at the Scrip Level and Accounting Variables: The Indian Evidence - Sen, Som Sankar; Ghosh, Santanu Kr. (Indian Journal of Finance, 2008)
This paper investigates empirically the relationship between stock liquidity at the scrip level and some selected accounting variable. Taking Amivest Liquidity Ratio as a measure of stock liquidity present study explores a significant positive relationship between market liquidity and growth of assets, growth of sales and Profit Before Interest and Taxes. But no significant relationship is established between market liquidity and corporate liquidity and only in a few stray cases significant relation between leverage and market liquidity is reported. The results from the Principal Component Analysis confirm a positive relation between the joint effect of growth of assets, growth of sales and Profit Before Interest and Taxes with the market liquidity at the scrip level.